Hazard identification and characterization for quality control of biltong through application of appropriate microbiology and biotechnology methods - Zyl, E.L. van; McCrindle, C.M.E.; Makita, K.; Grace, Delia (2011)
Background: The main objective of this study was to assess the safety of beef biltong produced and marketed by formal and informal channels and opportunities for processing and marketing of biltong by small scale cattle farmers. Processing biltong from communal cattle slaughtered at a small scale, registered abattoir, by small scale farmers, could increase value added income for farmers and improve nutritional security for consumers as it is a protein rich product with a long shelf life that does not require refrigeration. However, a communication and incentive strategy will have to be developed to alleviate microbiological food safety hazards in biltong in particular hazards due to unhygienic processing and marketing. Such a strategy requires better knowledge of the microbiological risks associated with biltong and the points at which they can be controlled. Methods: The study applied a combination of Hygiene Assessment, Hazard Analysis and Critical Control Point (HACCP) framework and Codex Alimentarius Commission microbiological risk assessment. Biotechnology (PCR) was used to check that the biltong originated form beef. Biltong samples were purchased from vendors in the Tshwane Municipal Area of Gauteng. Different biltong outlets were observed and described, including informal markets, biltong kiosks, service stations, supermarkets and butchers. Informal interviews and observations were used to construct a flow diagram illustrating the value chain for biltong. This has not previously been published. Microbiological cultures including E coli Type 1, Coliform Count, Total Plate Count and Staphylococcus aureus were conducted on 85 samples. Results: The microbiological results were compared to contamination risks identified along the food value chain for each outlet and a mitigation strategy developed. A market opportunity in informal markets catering to taxi commuters was identified. It was found that the added value to a beef carcass could increase income for small scale farmers and a financial model was tested in a rural community. Summary: Our study suggests biltong could contribute to sustainable livelihoods and nutritional security for the poor.